2017
DOI: 10.3382/ps/pew492
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indigenous Aseel chicken breed for morphological, growth, production, and meat composition traits from India

Abstract: Aseel is an important native chicken breed of India, known for its martial qualities (aggressive fighting abilities), pugnacity, and majestic gait. The aim of the study is to conserve and characterize the Aseel germplasm, which is considered to be endangered. The birds were maintained on deep litter under a simulated backyard type of housing having night shelter and a free-range area. A total of 313 chicks produced in the second generation from the flock collected from native tract in Andhra Pradesh was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
36
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 15 publications
14
36
9
1
Order By: Relevance
“…The higher leg proportions in the present study might be due to the native Aseel chicken which had stronger legs and rural purelines which were under selection for higher shank length. Similar findings were reported by many authors (Haunshi et al 2013;Padhi et al 2016;Rajkumar et al 2016;Rajkumar et al 2017) in native and crossbred chicken. Liver proportion was significantly (P ≤ 0.05) higher in crosses with rural purelines than the broiler crosses (Table 5).…”
Section: Carcass Traitssupporting
confidence: 92%
See 2 more Smart Citations
“…The higher leg proportions in the present study might be due to the native Aseel chicken which had stronger legs and rural purelines which were under selection for higher shank length. Similar findings were reported by many authors (Haunshi et al 2013;Padhi et al 2016;Rajkumar et al 2016;Rajkumar et al 2017) in native and crossbred chicken. Liver proportion was significantly (P ≤ 0.05) higher in crosses with rural purelines than the broiler crosses (Table 5).…”
Section: Carcass Traitssupporting
confidence: 92%
“…Many factors like breed, age, sex, nutrition, rearing systems and type of meat affects the composition of meat (Boskovic et al 2010) which might have caused the variations in present findings also. Similar findings of fat and ash proportion in Aseel chicken meat were observed by Rajkumar et al (2017). The higher ash proportion in Aseel crosses indicated high mineral content in the muscle.…”
Section: Proximate Compositionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies on meat composition showed that Aseel breast and thigh muscles meat contain 26.85 and 24.94% crude protein, 3.75 and 7.13% fat, and 88.28 and 83.35% dry matter (Haunshi et al, 2013). Rajkumar et al (2017) reported 21.5% crude protein, 3.4% fat, 2.0 ash and 73.3% moisture in Aseel breast meat.…”
Section: Meat Compositionmentioning
confidence: 98%
“…The Nicobari breed is an indigenous and endemic breed of chicken of Nicobar Islands which are an internationally acknowledged biodiversity hot spot, off the Indian mainland (got detached from Asian main-lands some 100 million years ago) and produces highest number of eggs among all indigenous chicken breeds of India [7] and is believed to have high disease resistance. Aseel is one of the important and most popular indigenous chicken breeds of Indian mainland and is well known for their meat quality with desirable taste and avor besides ability to thrive under adverse climatic and nutritional conditions [8]. Ghagus is another important native chicken breeds of coastal region of Southern India known for their meat quality with desirable taste and avor, disease resistance [9] and ability to perform under hot and humid climate and under low plane of nutrition.…”
Section: Introductionmentioning
confidence: 99%